An X- Ray Photoelectron Spectroscopic Examination of Glasses from the Se-S Alloy System - G. M. Saffarini; B. R. Orton (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Mixtures of sulphur and selenium have been prepared in the form of bulk glasses over the composition range Se, 10, to 50 at % S. X-ray diffraction measurements on these alloys give structure factors which have first sharp diffraction peaks (FSDP) indicating medium as well as short range order. To investigate possible local order, x-ray photoelectron spectroscopic (XPS) measurements have been obtained on these glasses. The emphasis of the measurements has concentrated on two features, (a) the valence band, which depends on the over-all density of states and (b) the plasmon energies from the 1,31v14.5Mos selenium Auger peaks which may be looked upon as being determined by the local electron density about the selenium atoms. It is found that the s-type peaks of the valence band split into two components between 15 and 40 at % S while the p-type peaks remain similar to pure selenium. The plasmon energies from the Auger peaks change markedly with composition. As sulphur is added to selenium the plasmon energy decreases, compared with the pure element, but sluts to increase at 20 at % S so that at a composition of 40 at % S the plasmon energy is the same as that of elemental selenium. A simple model is proposed to explain these results.